Visual and Verbal in Music Video Clip of The Script's Band Entitled 'The Man Who Can't Be Moved' - Dian Restiana Dewi, Putu; Maharani, Sang Ayu Isnu; Wandia, I Ketut (Humanis; Vol 24 No 1 (2020)DO - 10.24843/JH.2020.v24.i01.p02, 2020)
The title of this paper is “Visual and Verbal In Music Video Clip Of The Script’s Band Entaitled “The Man Who Can’t Be Moved”. The writing of this under graduate thesis aimed at finding out the messages from the lyrics of the music video clip applying theory of visual communication elements and the theory of meaning. It is also aimed at analyzing the use of visual and verbal communication elements as well as finding out correlation between the visual elements and verbal representation with the meaning of the song in this video clip.The aims of this study were to analyze the elements of visual communication and to find out the meanings of the song lyric. The method used in this study was library research method and it is supported by note taking technique. The data was qualitativelyanalyzed based on John Dyer’s theory (1993) and the theory of meaning by Geoffrey Leech (1974). It was found that the music video clip in the album The Script contained the 5 categories of visual communication such as appearance, manner, activity, props and setting, and visual or image. The meanings of the song lyrics found were conceptual and connotative meaning. The relationship between verbal and visual communication found that they were supporting each other.